2018
DOI: 10.1186/s12882-018-0829-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in clinicopathological characteristics and renal outcomes of Chinese patients with IgA nephropathy

Abstract: BackgroundThe prognostic effect of gender on immunoglobulin A nephropathy (IgAN) is not clear. We explored gender-related differences in clinicopathological features and renal outcomes in IgAN.MethodsThis was a single-centre retrospective study. Patients were divided into two groups according to gender. The clinicopathological features at biopsy and renal outcomes during the follow-up were collected and analysed. Renal outcomes were defined as the doubling of baseline serum creatinine and end-stage renal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
6
28
0
2
Order By: Relevance
“…Furthermore, all 4 patients demonstrating disease progression over the course of the 2-year follow-up were male. According to Deng et al [50], although female preponderance was evident in IgA nephropathy, male IgA patients presented with worse clinicopathologic features than female patients and higher rates of creatinine increase, which could support our result. Further research should be performed to investigate the impact of gender in IgA nephropathy prognosis.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, all 4 patients demonstrating disease progression over the course of the 2-year follow-up were male. According to Deng et al [50], although female preponderance was evident in IgA nephropathy, male IgA patients presented with worse clinicopathologic features than female patients and higher rates of creatinine increase, which could support our result. Further research should be performed to investigate the impact of gender in IgA nephropathy prognosis.…”
Section: Discussionsupporting
confidence: 82%
“…Similar result was obtained in an investigation including 24.886 elderly residents in a community [10]. A retrospective study of IgAN patients showed no significant differences observed in renal survival between male and female by SUA level-matching [30]. Another single-center retrospective cohort study showed that an elevated uric acid level was an independent risk factor for ESKD in female IgA patients but not male patients [5].…”
Section: Discussionsupporting
confidence: 75%
“…23,24 Consistent with European studies, males predominated (male : female, 2.4:1) in GRACE-IgANI, which is distinct from East Asian cohorts which report either equal incidence in males and females or even an increased frequency in females. [25][26][27][28] Similar to studies reported from China, at presentation males had more advanced disease with lower eGFR, more frequent hypertension and more fibrosis on kidney biopsy. 26 A metaanalysis of 25 studies in IgAN reported that male gender was associated with a worse outcome.…”
Section: Baseline Risk Of Progression In the Grace-igani Cohort Usingsupporting
confidence: 75%
“…[25][26][27][28] Similar to studies reported from China, at presentation males had more advanced disease with lower eGFR, more frequent hypertension and more fibrosis on kidney biopsy. 26 A metaanalysis of 25 studies in IgAN reported that male gender was associated with a worse outcome. 29 GRACE-IgANI will allow us to determine if this is true of South Asian males with longitudinal follow-up data.…”
Section: Baseline Risk Of Progression In the Grace-igani Cohort Usingsupporting
confidence: 75%